Increasing Learning Motivation of First Grade Elementary School Students Through Science Exhibition Activities in Theme-Based Learning (Universitas Pendidikan Indonesia Kampus Cibiru, 2024)
This study aims to evaluate the influence of science exhibitions on the learning enthusiasm of first-grade elementary school students. The exhibition was carried out through exploration and simple science experiments designed interactively and contextually. The methodology used was quantitative with a pre-experimental one-shot case study approach. The main measuring instrument, in the form of a questionnaire, was distributed to 73 students after the exhibition was completed. The findings showed that all indicators of student learning motivation were in the very good category, with the highest percentage reaching 94.52%. In addition, the validity test conducted using the Pearson Product Moment correlation method produced a value of 0.996, indicating a very strong relationship between science exhibition activities and increased student learning motivation. These results strengthen the idea that fun and contextual learning through science exhibitions can be an effective alternative to increase enthusiasm for learning, curiosity, and understanding of science concepts in children from an early age. Theoretically, this study contributes to the development of experiential and contextual learning approaches in science education. Practically, the findings provide guidance for educators and schools in designing interactive science learning activities that can enhance students’ motivation and engagement in elementary education.